Implementation of Village Development Planning Deliberations - Lia Afrianti; harmiati harmiti; Mulyadi Mulaydi (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2021)
In the village development planning process at the village level, there is a lack of fulfillment of the obligation to realize the capacity of a predetermined program, but it gives results in the implementation of the Village Development Planning Conference. This research uses descriptive analytical method with qualitative research. In this case the program that will be implemented and followed up in the District Development Planning Conference is still lack of skills in using technology, lack of transparency in the use of funds for the implementation of village development planning deliberations, lack of communication between village officials and BPD so that programs to be followed up still need to need space for realizing a village development program that will be implemented in the Village Development Planning Conference. That way, a recommendation is given and needs to be updated such as, lack of competence in technology and informant management, lack of transparency of budget allocations in the determination process, lack of communication between the implementing apparatus and the Village Consultative Body